ANALISIS PERBANDINGAN SIFAT FISIS DAN MEKANIS ALUMINIUM PADA BODY MOBIL LAND ROVER TAHUN 1982 YANG DI LAS DAN ROW MATERIAL - Aryananta Lufti; Budi Harjanto; Nurtjahyono; Silitonga, Frangky (JURNAL MEKANIKASISTA, 2024)
The main objectives of the research are stated in the documents provided, including: Knowing the strength of aluminum bodies, and analyzing the performance of bodies that frequently experience collisions. The scope of this research is the scope of this research includes evaluating the strength of aluminum and the welding process as well as tests carried out to evaluate the physical and mechanical properties of aluminum materials, including tensile, bending, hardness, composition and microstructural analysis tests. The research method used is a quantitative research method that emphasizes the results of experiments in a complete and measurable way, thereby providing a comprehensive understanding of the characteristics of aluminum in automotive applications. The results and findings of this research are. Overall, the research findings contribute to the understanding of aluminum characteristics in automotive applications, and offer implications for improving material selection, welding techniques, and structural design in the automotive sector. Opportunities that develop ahead utilizing the automotive industry can improve practices, products, and development processes, ultimately leading to advances in automotive engineering and design.